A Demand Model for the Local Public Sector - Deacon, Robert T. (The Review of Economics and Statistics, 1978)
IN recent years there have been notable advances in the methodology used in empirical studies of state and local public spending. The rather ad hoc econometric studies of the mid-1960s are being replaced by more carefully specified models, e.g., Barr and Davis (1966), Ohls and Wales (1972), Borcherding and Deacon (1972), and Bergstrom and Goodman (1973). Most of these efforts share the common feature that expenditures are viewed as responses to collectively exercised demands. While these studies have yielded insights, all have been partial equilibrium in nature and none has incorporated the possibility of substitution among public services in response to changes in relative costs. A goal of the present paper is to fill this gap by directly modeling and estimating such substitution effects in collective consumption. To accomplish this, it is convenient to view expenditure decisions in the public sector as analogous to consumer choices in the private sector, i.e., as if generated by utility maximization subject to a budget constraint. Quite aside from any advantages this approach holds for empirical analysis, this view of the public decision-making process has been highly attractive to theoretical researchers. Although the utility maximization paradigm has never been subjected to a direct empirical test, it has been employed to predict the effects of intergovernmental grants and spillovers across jurisdictions, and to examine other topics. A second aim of this analysis, therefore, is to provide empirical evidence on the tenability of this view of the local public sector.